Gamification of music lessons and factors affecting its use in private kindergartens in Beijing - Wang, Fang; Chieng, Julia; Loo, Fung Chiat (Human Resource Management Academic Research Society, 2023)
Musical games are an important part of kindergarten music education. This study aims to explore the current use of gamification in kindergarten music education in terms of both the frequency of gamification use and the factors that influence teachers’ use of gamification in music teaching and obtain suggestions to enhance teachers’ use of gamification in teaching. This is a qualitative study involving the research participants of 28 children and 3 teachers from the middle class (4–5 years old) of the Blue Sky Haiyue Bilingual Kindergarten in Beijing. A total of four music lessons were observed where three were singing and one was rhythmic, with two of the lessons used gamification. Interviews were conducted with the three teachers individually followed by a focus group discussion with them. Data analysis showed that gamification was not frequently used in the teaching of music. Factors that influence the use of gamification in teaching include the level of musical literacy among the teachers, the teachers’ attitude towards music, and the extent of attention towards music activities in the kindergarten. Recommendations for enhancing teachers’ gamification teaching include improving the teachers’ music literacy, encouraging children to participate in music games, and enriching the types of music lessons.